Foot wear of the horse - Schneider, Fred. L. (My University, 1902)
Introduction: Although the evolution of the present horse shoe from the primitive foot wear for draught animals used in ancient times furnishes an interesting subject for investigation very little has been written as a part of history that might make the subject the more vivid. Neither are there any passages in the Bible that relate to horse shoeing. Xenophon an early historian recommended various means for hardening the hoofs of horses and mules, and from this we are lead to assume that the ancients were ignorant of the art of farriery or horse shoeing. Ancient columns and marbles having on them representations of horses have, in only a few instances given evidence of shod hoofs. No allusion to shoeing is made by early writers on veterinary topics. There is abundant testimony, however, that the ancients did sometimes protect the feet of their beasts of burden. Wrappings of plaited fiber, as hemp or more commonly a kind of leathern sack or sandal which was sometimes provided with an iron sole were used by the ancients. In Great Britain of recent years horse shoes of a peculiar farm and pierced for nails have been unearthed while in Scotland ancient horse shoes have been found, consisting of a solid piece or iron very heavy and made to cover the whole hoof.
Citation: Schneider, Fred. L. Foot wear of the horse. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Equine; Hooves; Horseshoes; Farrier; Theses; Manuscripts (documents)